Supporting and Developing Talent in Technical Education in the Context of Industry 5.0 - Jaroslav KRIZ; Jaroslav VETESKA (Communications of International Proceedings, 2025)
Industry 5.0 has placed new demands on education, notably a greater emphasis on preparing graduates of technical fields for a labour market that is evolving quickly. A key part of this preparation is the support and development of talent, which provides the ground for innovation, creativity and the ability to respond to technological as well as social changes. This study examined how teachers at secondary schools and universities view talent support in technical education and how they assess its effect on graduates’ readiness for future employment. The study used a qualitative methodology based on focus group discussions. Thematic analysis of the data revealed that talent in technical education is seen as a dynamic phenomenon that is expressed in creativity, independent thinking and especially in the practical use of knowledge. Project-based teaching, participation in research and industrial projects, mentoring and dual study programmes are highlighted as the main forms of support. The results suggest that systematic work with talent increases graduates’ preparedness for the labour market in the era of Industry 5.0, where soft skills, adaptability, resilience and interdisciplinary cooperation are crucial.
Keywords: career readiness; Industry 5.0; interdisciplinary collaboration; talent development; technical education